A Parametric Approach to Performative-based Design, Case Study: Earth Tube Ventilation - (:unkn) unknown (My University, 2020)
As integrated design becomes more prevalent, new workflows develop in the architectural industry. Rather than the traditional sequential pattern, the knowledge is now being applied in parallel. That is, unlike the old baton passing, the players including the architect, the engineer, the consultant, the contractor, etc. play their role simultaneously. To achieve this, an architectural ecosystem needs a compatible digital information exchange approach; an approach that involves the engineer in the strategic design of systems, increases the chances of more creative, more integrated and higher-performing systems. There are some problems in the current parametric studies such as lack of inclusivity of all building physics facets, lack of validation, and lack of proper visualization in some cases. This dissertation intends to fill in these gaps by proposing a methodology to create a performance model integrated into a popular design tool, Rhinoceros 3D, of a rather rare ventilation system, the Earth Tube Ventilation. The idea is to keep all the simulation pieces in the same place that the 3D modeling happens. The model is further validated using the data from the experiments done on the Aldo Leopold Foundation building located close to Baraboo in Wisconsin. This process can be extended to other aspects of Performative Based Design.
Keywords: Earth Tube System; Hybrid Ventilation; Parametric Approach; Performative-Based Design; Python; Validation